Brief Treatment of Co-Occurring Post-Traumatic Stress and Depressive Symptoms by Use of Accelerated Resolution Therapy® - Kip, Kevin; Sullivan, Kelly L.; Lengacher, Cecile A.; Rosenzweig, Laney; Hernandez, Diego F.; Kadel, Rajendra; Kozel, F Andrew; Shuman, Amy; Girling, Sue Ann; Hardwick, Marian J.; Diamond, David M. (Frontiers in Psychiatry, 2013)
This uncontrolled prospective cohort study evaluated the use of Accelerated Resolution Therapy (ART) for treatment of comorbid symptoms of post-traumatic stress disorder (PTSD) and major depressive disorder (MDD). Twenty-eight adult subjects, mean age of 41 years (79% female, 36% Hispanic), received a mean of 3.7 + 1.1 ART treatment sessions (range 1-5). ART is a new exposure-based psychotherapy that makes use of eye movements. Subjects completed a range of self-report psychological measures before and after treatment with ART including the 17-item PCL-C checklist (symptoms of PTSD) and 20-item Center for Epidemiologic Studies Depression Scale (CES-D). For the PCL-C, the pre-ART mean (+ standard deviation) was 62.5 (8.8) with mean reductions of -29.6 (12.5), -30.1 (13.1), and -31.4 (14.04) at post-ART, 2-month, and 4-month follow up, respectively (p<0.0001 for comparisons to Pre-ART score). Compared to pre-ART status, this corresponded to standardized effect sizes of 2.37, 2.30, and 3.01, respectively. For the CES-D, the pre-ART mean was 35.1 (8.8) with mean reductions of -20.6 (11.0), -18.1 (11.5), and -15.6 (14.4) at post-ART, 2-month, and 4-month follow up, respectively (p<0.0001 compared to Pre-ART score). This corresponded to standardized effect sizes of 1.88, 1.58, and 1.09, respectively. Strong correlations were observed at 2-month and 4-month follow-up for post-treatment changes in PTSD and depression symptom scores (r=0.79, r=0.76, respectively, p<0.0002). No serious treatment-related adverse effects were reported. In summary, ART appears to be a promising brief, safe, and effective treatment for adults with clinically significant comorbid symptoms of PTSD and depression. Future controlled and mechanistic studies with this emerging therapy are warranted, particularly given its short treatment duration, and in light of current heightened emphasis on health care cost constraints.